Examining the potential impacts of geolocators on a small migratory songbird, the Golden-cheeked Warbler: results from a multi-year study - John N. Macey; Kellene R Collins; Michael D Gamble; Nathan Grigsby; Nancy M Raginski; Jane M Kunberger; Drew S Finn; Melanie R Colón; Shannon Carrasco; Ashley M. Long (Avian Conservation and Ecology)
Advancements in tracking technologies have improved our knowledge of migratory movements for many songbirds and simultaneously raised questions about how tracking devices may influence an individual’s survival and behavior. During a five-year study (2017–2021) at two study sites in central Texas, USA, we quantified the potential impacts of miniaturized light-level geolocators on a small (~10 g) Nearctic-Neotropical migratory songbird, the Golden-cheeked Warbler ( Setophaga chrysoparia ; hereafter warbler). We used generalized linear models to examine the effects of geolocator, age, and year on warbler pairing success, fledging success, and apparent annual return rates (hereafter return rates) at each study site. Most parameters we considered in our pairing success, fledging success, and return rate models were not statistically significant. However, at one study site, we found lower return rates for second year warblers with geolocators compared to second year and after second year warblers without geolocators. We also described warbler behavior immediately after we attached the geolocators, body condition upon their return, and body mass before and after carrying the devices. Most warblers resumed normal activities (e.g., singing, foraging) within 30 min after we attached the devices, showed no visible signs of injuries, and had similar body mass before and after carrying the geolocators. Overall, we did not find consistent evidence across sites or age classes that miniaturized light-level geolocators negatively impacted the Golden-cheeked Warbler responses we measured. However, we encourage continued research on this topic, especially as it relates to age-dependent effects of geolocator attachment on birds.